Challenging Global Finance - Friesen, Elizabeth. author. aut Link
XI, 220 p.
Keywords: Friesen demonstrates how transnational CSOs and NGOs can influence the context in which international political decisions are made. She shows how, by reframing the issues, the transnational campaign for the cancellation of third world debt altered the dominant discourse, shifted the agenda and thereby shaped political outcomes.